Systematic revision of Thaumastocoris Kirkaldy (Hemiptera: Heteroptera: Thaumastocoridae) - Noack, Ann E.; Cassis, Gerasimos; Rose, Harley A. (Zootaxa, 2011)
The genus Thaumastocoris is revised. Nine new species are described (T. busso, T. freomooreae, T. kalaako, T. majeri, T. nadeli, T. ohallorani, T. roy, T. safordi, and T. slateri) and the five previously described species are redescribed. A diagnostic key to species is provided, supported with illustrations of key character systems and maps depicting their distributional range. Host plants are tabulated, and biology and host plant associations are discussed.